ChemInform Abstract: Development of a Benzimidazole‐Derived Bidentate P, N‐Ligand for Enantioselective Iridium‐Catalyzed Hydrogenations. Issue 43 (21st October 2014) - Weemers, Jarno J. M.; Sypaseuth, Fanni D.; Baeuerlein, Patrick S.; van der Graaff, William N. P.; Filot, Ivo A. W.; Lutz, Martin; Mueller, Christian
Abstract Both enantiomers of the novel benzimidazole‐derived bidentate P, N‐ligand (I) are synthesized (not shown) and applied to Ir‐catalyzed hydrogenation reactions.